2017
DOI: 10.1126/sciadv.1602785
|View full text |Cite
|
Sign up to set email alerts
|

Generation of blue chrysanthemums by anthocyanin B-ring hydroxylation and glucosylation and its coloration mechanism

Abstract: Coexpression of two anthocyanin modification genes elicits blue flower coloration through interaction with colorless flavonoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 37 publications
2
113
0
1
Order By: Relevance
“…High-performance liquid chromatography was performed following the method of Noda et al (2013). The structures of the major anthocyanins detected in the current study were determined and reported by Noda et al (2017).…”
Section: Anthocyanin Analysismentioning
confidence: 99%
“…High-performance liquid chromatography was performed following the method of Noda et al (2013). The structures of the major anthocyanins detected in the current study were determined and reported by Noda et al (2017).…”
Section: Anthocyanin Analysismentioning
confidence: 99%
“…; Noda et al . , ). However, the content of Dp derivatives was higher than that of Cy derivatives in both V .…”
Section: Discussionmentioning
confidence: 99%
“…In chrysanthemums, a few regulatory genes involved in flower development have been isolated, such as MADS-box, TCP, and WUS-like genes [10][11][12]16]. Some important functional genes and transcription factors involved in the anthocyanin biosynthesis pathway have also been characterized including ANS, F3′H, F3H and MYB-like genes [13][14][15][16]. However, chrysanthemums have complex capitula containing two morphologically distinct florets and through a long period of breeding a variety of flower shapes and diverse colors have been created.…”
Section: Abce Models Have Revealed That A-class Together With E-classmentioning
confidence: 99%